Caminhos de resistência: do poder sindical ao poder político; memórias sobre lutas dos trabalhadores da USIMINAS (1960 1988) - Souza, Paulo Roberto de (2014)
The analysis of the background of workers from various areas of activity shows that capitalists impose processes of exploitation of the working class in order to generate even more capital. In the city of Ipatinga (MG), the building of a large steel mill involved changing habits of the local population, including the implementation of a strict discipline on employees the so-called USIMINAS culture . This disciplinary model also involved the control of workers local trade union, with the direct interference of the company in the elections, as it proves its attempts at preventing the formation of an oppositional slate intended to take control of the union in favor of the workers. By combining strength and daring, a group of laborers managed to form an opposition slate without rising suspicious and to make it official as early as possible, so that it ended as the first slate to be registered. Union elections in 1985 changed the everyday life of local population, who get involved directly in the struggle for votes. The company showed its determination by threatening directly or indirectly, if the opposition group won the elections. This strategy of threaten proved to be effective since the slate n. 2 won with explicit support of the company. The historical process of forming slate n. 1 shows that the bonds its members established with other workers families allowed most of them putting themselves in contention for local political power, right after being fired. As population was receptive to their proposal, in the 1985 municipal election these workers were able to gain political power in Ipatinga over traditional politicians and to deploy an administration with the participation of the people. Social conflicts from the early days of steel mill operation still permeate local memory and it seems strongly influenced the disputes in the 80s. In the game of oppression and resistance, workers challenged USIMINAS culture , which controlled their actions and population s. Since workers won in the municipal elections, spaces formerly occupied by political oligarchy and the company had to be divided between this latter and them, who had been fired as a punishment for their opposition actions to the union administration.